Diagnóstico de la gestión empresarial de los emprendimientos PYMES comerciales de la ciudad de Riobamba. - Shagñay Astudillo, Jhoan Fernando (2025)
This research focuses on diagnosing business management in commercial SME ventures in Riobamba. It aims to identify their primary strengths and weaknesses, as well as to understand their management dynamics. The objective was to analyze the business management of commercial SME ventures in Riobamba. The methodology used was quantitative, descriptive, non-experimental, and correlational. Among the main results, these businesses show diverse characteristics and a tendency toward informality in some administrative processes. There are also limitations in strategic planning and the weak use of technological tools. It was concluded that many surveyed SMEs lack defined structures, updated business plans, and effective internal control. Those with higher managerial training demonstrate better performance. Although these SMEs have a functioning operational foundation, they lack clear technical or strategic principles. Therefore, it is necessary to apply business models focused on organizational transformation to enhance competitiveness.